2020
DOI: 10.1111/ijlh.13222
|View full text |Cite
|
Sign up to set email alerts
|

Significance of CD10 protein expression in the diagnostics of follicular lymphoma: A comparison of conventional immunohistochemistry with flow cytometry supported by the establishment of BCL2 and BCL6 rearrangements

Abstract: IntroductionHistopathological examination and immunohistochemistry (IHC) with a crucial role of CD10 expression remain a standard diagnostic tool in follicular lymphoma (FL). The results of IHC CD10 detection with different primary antibodies are not fully reproducible, but some reports show that flow cytometry (FCM) can be a reliable method of CD10 identification.MethodsThe aim of the study was to compare results of CD10 expression in FL by IHC and FCM including immunophenotypic features in the context of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Pre-therapeutic lymphoma samples as cellular suspensions were also obtained by the same hematopathologist by FNAB/ultrasound-guided FNAB from the involved lymph nodes or tumors of patients diagnosed at Maria Sklodowska-Curie National Research Institute of Oncology between 2016 and 2017. Each case, obtained by FNAB, was also followed by detailed FCM immunophenotyping, assessment of % of pathological cells, and cytogenetics analysis as previously described [86]. Subjects submitted for lymphadenopathy screening and with reactive histopathological findings served as controls.…”
Section: Collection Of Fnab Samples and Clinical Informationmentioning
confidence: 99%
“…Pre-therapeutic lymphoma samples as cellular suspensions were also obtained by the same hematopathologist by FNAB/ultrasound-guided FNAB from the involved lymph nodes or tumors of patients diagnosed at Maria Sklodowska-Curie National Research Institute of Oncology between 2016 and 2017. Each case, obtained by FNAB, was also followed by detailed FCM immunophenotyping, assessment of % of pathological cells, and cytogenetics analysis as previously described [86]. Subjects submitted for lymphadenopathy screening and with reactive histopathological findings served as controls.…”
Section: Collection Of Fnab Samples and Clinical Informationmentioning
confidence: 99%
“…However, MUM1 had an adverse effect in the patients with CD10 negative. OS and PFS in the group with MUM1 positive/CD10 negative decreased significantly for 5 years than in the group [25,26]. The positive rate of MUM1 was 44.4%, higher than in the studies of Kikeri N. Naresh (37%), Eric D Hsi (14.4%) [16,22].…”
Section: Clinical Datamentioning
confidence: 69%
“…Luc Xerri also recommended that MUM1 can be used as a routine biomarker for the clinical management of patients with FL [15]. Otherwise, Anna Szumera-Cieckiewicz, et al suggested that the lack of CD10 expression corresponded to the absence of Bcl2 and higher expression of MUM1, but had no impact on long-term outcomes [25]. Perhaps, for patients with FL with negative CD10, a further evaluation of MUM1 should be considered as an additional prognostic factor.…”
Section: Clinical Datamentioning
confidence: 99%